Recent Advances in Systems, Control and Information Technology : Proceedings of the International Conference SCIT 2016, May 20-21, 2016, Warsaw, Poland /: Proceedings of the International Conference SCIT 2016, May 20-21, 2016, Warsaw, Poland. (2017) - Unknown
No abstract available